1996
DOI: 10.1177/0361198196153000112
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Stone Matrix Asphalt Mortars

Abstract: The use of stone matrix asphalt (SMA) has continued to increase in the United States since its initial application in 1991. This preference for SMA has been linked to its ability to withstand heavy traffic without rutting. The antirutting capability of SMA is normally accredited to the presence of a stone-on-stone aggregate skeleton in the mixture. However, the mortar in an SMA mixture is also important. The mortar is composed of fine aggregate, filler, asphalt cement, and a stabilizing additive. Work to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous studies reported on the significance and applicability of the Superpave Ò protocols and equipment such as the Dynamic Shear Rheometer (DSR) and Bending Beam Rheometer (BBR) for the investigation of mastics and fine mortars [3,10]. Following these recommendations, the rheological properties were investigated by Dynamic Shear Rheometer (DSR) using 25 mm samples at three different temperatures 52°C, 58°C and 64°C for PG58-28 and 58°C, 64°C and 70°C for PG64-28.…”
Section: Temperature Sweep Testmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported on the significance and applicability of the Superpave Ò protocols and equipment such as the Dynamic Shear Rheometer (DSR) and Bending Beam Rheometer (BBR) for the investigation of mastics and fine mortars [3,10]. Following these recommendations, the rheological properties were investigated by Dynamic Shear Rheometer (DSR) using 25 mm samples at three different temperatures 52°C, 58°C and 64°C for PG58-28 and 58°C, 64°C and 70°C for PG64-28.…”
Section: Temperature Sweep Testmentioning
confidence: 99%
“…An increase in Al 2 O 3 , SiO 2 , SAF (combined SiO 2 , Al 2 O 3 , and Fe 2 O 3 ) and D 10 results in a decrease in the stiffening rate for both types of binders which can be an indication of plasticizing (softening). On the other hand, higher CaO, SO 3 and LOI values result in an increase in the stiffening rate, which identifies stiffer mastics. The highlighted values in Tables 7 and 8 reflect the statistically significant factors influencing the stiffening rate of mastics.…”
Section: Materials Idmentioning
confidence: 99%
See 2 more Smart Citations
“…The better performance of Stone Matrix Asphalt (SMA) is attributed to better coarse aggregate skeleton in these mixes compared to the dense graded HMA (Brown et al 1998;Scherocman 1991). The Bailey method of gradation selection (Vavrik et al 2001) reportedly produces an aggregate blend that is packed together in a systematic manner, to form an aggregate skeleton with the required interlock and packing.…”
Section: Introductionmentioning
confidence: 99%